Detection of a novel SETBP1 variant in a Chinese neonate with Schinzel–Giedion syndrome - Yang, Hansong; Liu, Zhiyong; Chen, Dongmei; Lin, Weiru; Wang, Lin; Chen, Tianfeng; Wang, Ruiquan; Yan, Xialin (Frontiers in Pediatrics, 2022)
Schinzel–Giedion syndrome (SGS) is a multiple malformation syndrome characterized by typical facial features, severe neurodevelopmental delay, and multiple congenital abnormalities. SGS is associated with de novo pathogenic variants in the SETBP1 gene. In specific, SETBP1 variants in over 50 patients with classical or non-classical SGS were clustered within exon 4. A male Chinese neonate with dysmorphic facial features, nervous system disorders, and organ malformations at birth was examined in this study and long-term followed-up. Whole-exome sequencing was performed to identify any underlying pathogenic variants in the proband. Additionally, we reviewed the literature that documents the main clinical features and underlying variants of all patients genetically diagnosed with SGS. The neonate had a characteristic midface retraction, abnormal electroencephalogram waveforms, and genital abnormalities. The patient did not initially develop hydronephrosis or undergo a comprehensive skeletal assessment. Six months after birth, the patient had an epileptic seizure and experienced persistent neurodevelopmental delay with auditory and visual abnormalities. Color Doppler ultrasonography at 18 months revealed hydronephrosis and bilateral widening of the lateral ventricles. The patient died suddenly 20.5 months after birth. Whole-exome sequencing revealed a heterozygous de novo variant (c.2605A > G:p.S869G) in exon 4 degradation sequence in SETBP1. The reported de novo heterozygous variant in SETBP1 (c.2605A > G:p.S869G) broadens the knowledge of the scientific community's on the possible SGS genetic alterations. To the best of our knowledge, this is the first report of SETBP1 variant (c.2605A > G:p.S869G) in SGS. The clinical manifestations of neonatal SGS are atypical, and genetic testing is crucial for diagnosis. Long-term follow-up should be conducted after diagnosis to optimize the therapeutic interventions.